An Analog Front-end Amplifier with Seamless Discrete Time-gain Compensation for Ultrasound Scanner - Son, Min-Hyeong; Um, Ji-Yong (Journal of semiconductor technology and science, 2023)
This paper proposes an analog front-end (AFE) amplifier with seamless discrete time-gain compensation (TGC) for ultrasound scanners. The AFE amplifier consists of a preamplifier and a programmable gain amplifier (PGA). A real-time TGC operation is typically accomplished with gradual gain increments in PGA. To achieve a seamless gain transition in PGA, this work proposes a preset switching scheme for an initialization of operating points in PGA. In addition, current-reuse operational amplifiers with dynamic push-pull current sources are deployed in the AFE amplifier to further enhance a transient response. The proposed AFE implemented in a 180-nm BCD process occupies 0.19 mm2, and consumes 2.3 mW. The AFE achieves a gain range from 34.3 dB to 50.5 dB with four gain steps, and a transient interval less than 18 ns during a gain transition. KCI Citation Count: 0